1996
DOI: 10.1148/radiology.198.3.8628859
|View full text |Cite
|
Sign up to set email alerts
|

Transthoracic needle biopsy with a coaxially placed 20-gauge automated cutting needle: results in 122 patients.

Abstract: Coaxial TNB performed with an automated cutting needle helps provide a diagnosis in the majority of patients with focal chest disease and is particularly useful in the diagnosis of benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
181
3
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 290 publications
(218 citation statements)
references
References 0 publications
30
181
3
4
Order By: Relevance
“…The 93% accuracy rate with percutaneous hilar biopsies seen in this study is comparable to the accuracy rates reported with a combination of endobronchial ultrasound-and EUS-guided FNAB 14 and is at the upper end of the range for the accuracy rates reported for image-guided mediastinal biopsies (78%-94%) [8][9][10][11][12][13] and lung biopsies (88%-95%). [3][4][5][6][7]24,25 The diagnostic yield of endobronchial ultrasound may be increased by electromagnetic navigation techniques that allow biopsy of endobronchially invisible pulmonary lesions. 26 EUS-guided procedures allow only fine-needle aspiration of individual cells, which is usually sufficient for staging purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 93% accuracy rate with percutaneous hilar biopsies seen in this study is comparable to the accuracy rates reported with a combination of endobronchial ultrasound-and EUS-guided FNAB 14 and is at the upper end of the range for the accuracy rates reported for image-guided mediastinal biopsies (78%-94%) [8][9][10][11][12][13] and lung biopsies (88%-95%). [3][4][5][6][7]24,25 The diagnostic yield of endobronchial ultrasound may be increased by electromagnetic navigation techniques that allow biopsy of endobronchially invisible pulmonary lesions. 26 EUS-guided procedures allow only fine-needle aspiration of individual cells, which is usually sufficient for staging purposes.…”
Section: Discussionmentioning
confidence: 99%
“…1 Currently, the most important prognostic factor for localized lung cancer is metastatic involvement of the mediastinal and hilar lymph nodes. 2 Transthoracic percutaneous needle biopsy (PNB) is routinely used to diagnose parenchymal [3][4][5][6][7] and accessible mediastinal [8][9][10][11][12][13] neoplasms.…”
mentioning
confidence: 99%
“…CT affords good visualization of all thoracic structures and CT guided biopsy has an accuracy for diagnosing malignancy of 80-95% [131,132]. It is the procedure of choice for sampling peripheral nodules (v2 cm in diameter) as the yield for transbronchial needle biopsy, in the absence of an endobronchial lesion, falls from 92-95% to 50-80% [132].…”
Section: Image Guided Needle Biopsymentioning
confidence: 99%
“…It is the procedure of choice for sampling peripheral nodules (v2 cm in diameter) as the yield for transbronchial needle biopsy, in the absence of an endobronchial lesion, falls from 92-95% to 50-80% [132]. FNA is the preferred sampling method of parenchymal nodules in order to reduce the incidence of complications and is known to have a similar sensitivity in detecting malignancy as core biopsy [131]. However, small tissue fragments for histological evaluation can generally be obtained with 19-22 gauge needles in 40-75% of patients [132].…”
Section: Image Guided Needle Biopsymentioning
confidence: 99%
See 1 more Smart Citation